Manual engagement and automation in amateur photography. Issue 1 (February 2018) - Ploderer, Bernd; Leong, Tuck Wah
Automation has been central to the development of modern photography and, in the age of digital and smartphone photography, now largely defines everyday experience of the photographic process. In this article, we question the acceptance of automation as the default position for photography, arguing that discussions of automation need to move beyond binary concerns of whether to automate or not and, instead, to consider what is being automated and the degree of automation couched within the particularities of people's practices. We base this upon findings from ethnographic fieldwork with people engaging manually with film-based photography. While automation liberates people from having to interact with various processes of photography, participants in our study reported a greater sense of control, richer experiences and opportunities for experimentation when they were able to engage manually with photographic processes.